2021
DOI: 10.1101/2021.10.18.464819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic KRASG12C inhibition drives effective interferon-mediated anti-tumour immunity in immunogenic lung cancers

Abstract: The recent development and approval of KRASG12C inhibitors promises to change profoundly the clinical management of lung cancer patients harbouring KRASG12C mutations. However, early clinical data indicate that acquired drug resistance can frequently develop after the initial response. Due to the immunosuppressive nature of the signaling network controlled by oncogenic KRAS, targeted KRASG12C inhibition can indirectly affect anti-tumour immunity. This has served as a rationale for combination with immune check… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…It has been reported that oncogenes such as MYC and KRAS can regulate immune response by suppressing IFN‐I pathways in various cancers. For example, the combined actions of endogenously expressed mutant KRAS and modestly deregulated MYC expression led to NK cell‐mediated immune escape through inhibition of IFN‐I pathways in pancreatic ductal adenocarcinoma and lung cancer [ 46 , 47 ]. Overexpression of MYC suppresses the recruitment and activation of immune cells by inhibiting the induction of interferon signaling in triple‐negative breast cancer [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that oncogenes such as MYC and KRAS can regulate immune response by suppressing IFN‐I pathways in various cancers. For example, the combined actions of endogenously expressed mutant KRAS and modestly deregulated MYC expression led to NK cell‐mediated immune escape through inhibition of IFN‐I pathways in pancreatic ductal adenocarcinoma and lung cancer [ 46 , 47 ]. Overexpression of MYC suppresses the recruitment and activation of immune cells by inhibiting the induction of interferon signaling in triple‐negative breast cancer [ 48 ].…”
Section: Discussionmentioning
confidence: 99%